Percutaneous Cryoablation of Pulmonary Metastases from Colorectal Cancer - Yamauchi, Yoshikane (Public Library of Science, 2011)
OBJECTIVE: To evaluate the safety and efficacy of cryoablation for metastatic lung tumors from colorectal cancer. METHODS: The procedures were performed on 24 patients (36–82 years of age, with a median age of 62; 17 male patients, 7 female patients) for 55 metastatic tumors in the lung, during 30 sessions. The procedural safety, local progression free interval, and overall survival were assessed by follow-up computed tomographic scanning performed every 3–4 months. RESULTS: The major complications were pneumothorax, 19 sessions (63%), pleural effusion, 21 sessions (70%), transient and self-limiting hemoptysis, 13 sessions (43%) and tract seeding, 1 session (3%). The 1- and 3-year local progression free intervals were 90.8% and 59%, respectively. The 3-years local progression free intervals of tumors ≤15 mm in diameter was 79.8% and that of tumors >15 mm was 28.6% (p = 0.001; log-rank test). The 1- and 3-year overall survival rates were 91% and 59.6%, respectively. CONCLUSION: The results indicated that percutaneous cryoablation is a feasible treatment option. The local progression free interval was satisfactory at least for tumors that were ≤15 mm in diameter.